PENTINGNYA PERAN ORANGTUA DALAM MEMBENTUK KEPRIBADIAN ANAK - Samsudin Samsudin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2019)
The role of parents in the formation of children's personality is very important, in forming the personality of parents must be a figure or give a good example early on, because it can affect the child to grow up to become an adult. The child's personality is formed depending on how parents educate, nurture and apply morals to the child since childhood, so that later in adulthood the child will get used to what is taught by both parents. The formation of the child's personality is not easy for parents, because if parents overestimate the formation of personality and character of children, then children will grow up to become children who often commit fraud, therefore parents must really pay attention to the importance of the formation process the personality of children from an early age and provide a good example also familiarizes with good things so that children grow up to be children who have good personalities and have good characters too.